Women’s Struggle Reflected in Divakaruni’s The Palace of Illusions: A Feminist Approach - Senly Darryl Augie; Siti Hanifa (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
Gender equality between men and women has been attained in plenty of countries during the past few centuries as the battle for women’s rights has progressed. This research concentrates on the female characters, specifically Draupadi and Amba. The objective of this research is to discover how female characters fight for equality in Divakaruni’s The Palace of Illusions. This research evaluates the data using qualitative methods and Naomi Wolf’s power feminism. The findings indicate that Draupadi strives for equality by wielding power, collaborating with a man, respecting another woman’s beauty choice, being able to voice her opinions, and making significant decision-making. Meanwhile, Amba decides to utilize her power, gain advantage of male strength, and take responsibility to fulfill her own needs.